Representation of Women Writers in Galician Emigration Press in Buenos Aires: Avelina Valladares and Rosalía de Castro as Displayed in Galician Almanac [Almanaque Gallego] (1898–1927) - Irene Jones (Humanities, 2022)
Galician Almanac in Buenos Aires [Almanaque Gallego de Buenos Aires] (1898–1927), founded and directed by Manuel Castro López, consists of a true collection of Galician knowledge made up of numerous works of historical and literary research by intellectuals and writers from both sides of the Atlantic. In its pages there are plenty of references to two contemporary fellow writers who have attracted our attention and become the subject of this brief study: Avelina Valladares and Rosalía de Castro. This paper examines the differences and proximities in the representation of women writers as highlighted by the magazine around these authors, considering that they are misadjusted characters in terms of the behavior standards of their time. In this sense, our study analyses how the Almanac… retrieves an imagery of the origins around the Galician emigrates, by pointing out that both Rosalia de Castro and Avelina Valladares took part in the setting of new literary and political standards. By this, the Almanac builds upon these women the sense of a new beginning for Galician emigrates in America.